PRODUKSI DAN KANDUNGAN NUTRISI DUCKWEED SEBAGAI ALTERNATIF SUPLEMEN PAKAN TERNAK DAN PUPUK ORGANIK PADA BERBAGAI TINGKAT INTENSITAS CAHAYA - Donatus Kantur; Antonius Jehemat (Politeknik Pertanian Negeri Kupang, 2018)
Duckweed is one of water plant that have wade potential to developed as new feed resource or to expansion of sustainable agriculture. For sustainable agriculture, any study on any location and session. Therefore, a research was conducted on goal to know the optimal light intensity onproduction and nutrient content of duckweed.This research conducted by factorial design, consist of two strain of duckweed, namely Lemna sp and Spirodella sp, and four level of light intensity, namely 100%, 70%, 50%, and 30%, of each. The parameter observed were temperature of water as cultivation media, cultivation media acidity, cultivation media decrease, plant fresh weight, dry matter and the proximate content, and NPK content of plant. The result show that there is high significant (P<0,01) interaction between duckweed strain with light intensity, cultivation media acidity, cultivation media volume decrease, fresh weight, and dry matter of duckweed. The best of fresh weight and dry matter of Lemna sp.shown on 70% light intensity but on 50% light intensity for Spirodella sp.